Pengembangan Fitur Video Pembelajaran untuk Mendukung Meteri Pembelajaran Digital Secara Online pada SMK Miftahul Huda - Imam Solikin (Journal of Applied Informatics and Computing, 2020)
This research is a development from previous research in the form of digital module learning media, the development carried out is in the form of adding features that contain learning videos to support digital learning materials online. This research was conducted at SMK Miftahul Huda, which is located at Jalan Lintas Timur Km 124, Tugu Agung Village, Lempuing District, Ogan Komering Ilir Regency. During the Covid 19 pandemic, the teaching and learning process at many schools was hampered in the delivery of material, because there were no meetings. face to face to convey material. Most of the delivery of material currently only uses WhatsApp in the form of photos of the material and examples of this make students confused in understanding the material, examples and doing their assignments. The method used in the development of the instructional video features to support online digital learning materials at Miftahul Huda Vocational High School is linear sequential model. The solution to the problems faced by SMK Miftahul Huda is by developing learning media in the form of a learning system equipped with videos and online digital materials that can be accessed using a smartphone. This developed learning system can make it easier to get material and examples that are attached with learning videos so that it makes it easier for students to learn and increase interest in learning